Tantangan Penerjemahan Arab-Indonesia Video Animasi Qisshah Al-Athfâl dalam Pendidikan Moral Anak - Mauidlotun Nisa; Ulya Afifa (IAIN Madura, 2023)
This article reveals the challenges of translating the Qisshah Al-Athfal animated video which was uploaded by Zad Al-Horof through his YouTube account as a moral education for children. Translating animated videos that adapt voiceovers is an option in presenting moral education to children because hearing is the first active sense, so it is stronger than reading skills. This article examines the process of translating the animated video Qisshah Al-Athfal uploaded by Zad Al-Horof and refers to the adaptation of dubbing with a cultural approach and sosiolinguistic. There were four translated videos, all of which were chosen because of the precarious and tense situation in the setting of the story. Secondary sources are taken from the literature of books relevant to the translation process, ranging from several Arabic-Indonesian dictionaries to authoritative articles to be associated with this study. From the research results, it was found that in the translation process, politeness in language as Indonesian culture is highlighted, especially in translating my pronouns into